PsycEXTRA Dataset 2004
DOI: 10.1037/e723672011-001
|View full text |Cite
|
Sign up to set email alerts
|

Declining employment among young black less-educated men: The role of incarceration and child support

Abstract: In this paper, we document the continuing decline in employment and labor force participation of black men between the ages of 16 and 34 who have a high school education or less. We explore the extent to which these trends can be accounted for in recent years by two fairly new developments: (1) The dramatic growth in the number of young black men who have been incarcerated; and (2) Strengthened enforcement of child support policies. We use micro-level data from the Current Population Survey Outgoing Rotation G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 14 publications
1
88
0
Order By: Relevance
“…As the previous discussion highlighted, research has found that shifts in labor markets vary by race and that economic downturns may have greater criminogenic effects on blacks (Crutchfield, 1995, p. 205; see also Holzer, Offner, & Sorensen, 2005;Parker, 2008). Scholars also have found divides among ex-prisoners seeking employment; black ex-prisoners, for 826 MEARS ET AL.…”
Section: Labor Markets Prisoner Reentry and Racementioning
confidence: 93%
“…As the previous discussion highlighted, research has found that shifts in labor markets vary by race and that economic downturns may have greater criminogenic effects on blacks (Crutchfield, 1995, p. 205; see also Holzer, Offner, & Sorensen, 2005;Parker, 2008). Scholars also have found divides among ex-prisoners seeking employment; black ex-prisoners, for 826 MEARS ET AL.…”
Section: Labor Markets Prisoner Reentry and Racementioning
confidence: 93%
“…23 And it is important to note that these calculations are all based on studies that include only those individuals who report positive earnings in any given year. Those with zero earnings Á either due to incarceration, disability, death, or any other reason resulting in permanent labor force withdrawal Á are not captured in these data, and, at least among minority men, the incidence of those with zero earnings has grown (Holzer, Offner, and Sorensen 2005). Their growing absence from the data likely implies downward biases in the Journal of Children and Poverty 47 true estimates today, although the growth of earnings among low-income women in the 1990s (Blank 2002) might offset this to some degree.…”
Section: Forgone Productivity and Earningsmentioning
confidence: 98%
“…In addition, there is a gap in the literature about jail inmates' child support orders by gender. Given that mothers primarily have custody, mostly men have child support orders that are beyond their means to pay, which is relevant because nonpayment of child support is a criminal offense that can lead to reincarceration-and mothers lose material support (Holzer, Offner, & Sorensen, 2005).…”
Section: Parenthoodmentioning
confidence: 99%